Methane emissions reduce the radiative cooling effect of a subtropical estuarine mangrove wetland by half. (15th July 2020) - Liu, Jiangong; Zhou, Yulun; Valach, Alex; Shortt, Robert; Kasak, Kuno; Rey‐Sanchez, Camilo; Hemes, Kyle S.; Baldocchi, Dennis; Lai, Derrick Y. F.
Abstract: The role of coastal mangrove wetlands in sequestering atmospheric carbon dioxide (CO2 ) and mitigating climate change has received increasing attention in recent years. While recent studies have shown that methane (CH4 ) emissions can potentially offset the carbon burial rates in low‐salinity coastal wetlands, there is hitherto a paucity of direct and year‐round measurements of ecosystem‐scale CH4 flux (FCH4 ) from mangrove ecosystems. In this study, we examined the temporal variations and biophysical drivers of ecosystem‐scale FCH4 in a subtropical estuarine mangrove wetland based on 3 years of eddy covariance measurements. Our results showed that daily mangrove FCH4 reached a peak of over 0.1 g CH4 ‐C m −2 day −1 during the summertime owing to a combination of high temperature and low salinity, while the wintertime FCH4 was negligible. In this mangrove, the mean annual CH4 emission was 11.7 ± 0.4 g CH4 ‐C m –2 year −1 while the annual net ecosystem CO2 exchange ranged between −891 and −690 g CO2 ‐C m −2 year −1, indicating a net cooling effect on climate over decadal to centurial timescales. Meanwhile, we showed that mangrove FCH4 could offset the negative radiative forcing caused by CO2 uptake by 52% and 24% over a time horizon of 20 and 100 years, respectively, based on the corresponding sustained‐flux global warming potentials. Moreover, we found that 87% and 69% of the total variance of daily FCH4 could be explained by the random forest machine learning algorithm and traditional linear regression model, respectively, with soil temperature and salinity being the most dominant controls. This study was the first of its kind to characterize ecosystem‐scale FCH4 in a mangrove wetland with long‐term eddy covariance measurements. Our findings implied that future environmental changes such as climate warming and increasing river discharge might increase CH4 emissions and hence reduce the net radiative cooling effect of estuarine mangrove forests. Abstract : Results of 3 year eddy covariance measurements in a subtropical estuarine mangrove wetland showed annual mean net ecosystem exchange of CO2 and CH4 of −782 ± 101 g CO2 ‐C m −2 year −1 and 11.7 ± 0.4 g CH4 ‐C m −2 year −1, respectively. Mangrove CH4 emissions could offset 52% and 24% of the negative radiative forcing caused by CO2 uptake over a time horizon of 20 and 100 years, respectively, based on the respective sustain‐flux global warming potential metrics.